Monetary policy and core inflation - Michele Lenza (Deutsche Bundesbank, 2007)
This paper studies optimal monetary policy responses in an economy featuring sectorial heterogeneity in the frequency of price adjustments. It shows that a central bank facing heterogeneous nominal rigidities is more likely to behave less aggressively than in a fully sticky economy. Hence, the supposedly excessive caution in the conduct of monetary policy shown by central banks could be partly explained by the existence of a relevant sectorial dispersion in the frequency of price adjustments.
Keywords: E58; E52; E43; 330; core inflation; elasticity of intertemporal substitution; heterogeneity; nominal rigidity; Geldpolitik; Inflationsrate; Preisspanne; Branche; Preisrigidität; Substitutionselastizität; Zeitpräferenz; Theorie